Consumer Behavior Under Water Scarcity Conditions: How Perceived Mutability Influences Pro-Environmental Behavior - Figueiredo, Ana Catarina Mendes Gil Correia (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence